A failure scenario of ceramic laminates with strong interfaces. (November 2016) - Náhlík, Luboš; Štegnerová, Kateřina; Máša, Bohuslav; Hutař, Pavel
Highlights: Paper explains in detail scenario of damage mechanism of layered ceramic composite. The reason for crack bifurcation in the compressive layer is explained. The paper contributes to the better understanding of damage of ceramic laminates. Abstract: Over the last years many researchers have put a lot of effort into designing layered structures combining different materials in order to improve low fracture toughness and mechanical reliability of ceramics. It has been proven that an effective way is to create layered ceramics with strongly bonded interfaces. Significant internal residual stresses are developed within the composite layers after the cooling process from the sintering temperature, due to the different coefficients of thermal expansion of individual composite constituents. Residual stresses can significantly change the crack behaviour. Suitable choice of material of layers and ratio between layer thicknesses can lead to higher value of the so-called apparent fracture toughness, i.e. higher resistance of the ceramic laminate to the crack propagation. The paper deals with a description of the specific crack behaviour in the layered alumina–zirconia ceramics. Attention is devoted to the differences in the stress field description in the vicinity of the crack front. Two-dimensional and three-dimensional numerical models are developed for this purpose. The main aim is to clarify crack behaviour in the compressive layer and provide computational tools for estimation of crack behaviour in the field of strong residual stresses. The crack propagation is investigated on the basis of linear elastic fracture mechanics. Fracture parameters are computed numerically and by routines of authors. The sharp change of the crack propagation direction is estimated using the Sih's criterion based on the strain energy density factor, and conditions for crack bifurcation are determined. Estimated crack behaviour is qualitatively in a good agreement with experimental observations.